The level of information technology achievement among students and their practice of innovative problem-solving strategy (TRIZ) - Ali Salim Rashid Alghafri; Marwa Abdallah Rashid Alshafaa (International Journal of Evaluation and Research in Education (IJERE), 2026)
In today’s rapidly advancing digital landscape, equipping students with strong competencies in information technology (IT) and innovative problem-solving strategies is essential to meet market demands, foster lifelong learning, and engage with emerging technologies such as artificial intelligence. Theory of Inventive Problem Solving (TRIZ) has been applied in educational contexts to enhance students’ creativity and technical skills, yet prior research has produced mixed results regarding its effectiveness in robot construction and programming. This study investigated the impact of TRIZ-based instruction on IT achievement among 7th-grade students, examining differences between pre- and post-intervention performance and gender-related variations in robot assembly, programming, and strategy use. This aspect uniquely distinguishes the present study from prior investigations. Employing a descriptive correlational design, the sample comprised 329 7th-grade students and 65 IT teachers. Results indicated significant improvement in IT achievement from pre-test to post-test, favoring the post-intervention outcomes. However, no significant gender differences were found in post-test scores or in the application of TRIZ strategies. The findings highlight the value of integrating TRIZ-based approaches into IT curricula and diversifying problem-solving activities to cultivate innovation, technical proficiency, and adaptability among school students in preparation for future technological challenges.